Ogilvy on advertising - Ogilvy, David (New York: Vintage Boooks, 1985)
Overture. How to produce advertising that sels. Jobs in advertising-and how to get them. How to run an advertising agency. how to get clients. Open letter to a client in search of an agency. Wanted: a renaissance in print advertising. How to make TV commercials that sell. Advertising corporations. How to advertise foreing travel. The secrets of success in business to business advertising. Direct mail, my first love and secret weapon. Advertising for good causes. Competing with procter y gamble. Miracles of research.
Keywords: Publicidad